RNA sequencing profiles reveals progressively reduced spermatogenesis with progression in adult cryptorchidism - Sun, Weihao; Zhang, Xinhui; Wang, Lei; Ren, Guanyu; Piao, Shuguang; Yang, Chenghua; Liu, Zhiyong (Frontiers in Endocrinology, 2023)
Introduction The fertility of cryptorchidism patients who didn’t perform corrective surgery will decrease with age. Herein, we elucidate the histological alterations and underlying molecular mechanism in patients with an increase in the disease duration from 20 to 40 years. Methods Testicular tissues were obtained from three patients with cryptorchidism, ranging in age from 22 to 44 years. Three benign paracancerous testicular samples of matched ages were used as controls. The normal and undescended testicular tissues were stained with hematoxylin and eosin (HE) and immunofluorescence and all six testicular samples were subjected to RNA sequencing. RNA sequencing data were subjected to gene set enrichment analysis (GSEA), Kyoto Encyclopedia of Genes and Genomes (KEGG), protein-protein interaction (PPI) network analysis, and Gene Ontology (GO) searches. Real-time reverse transcriptase polymerase chain reaction was used to confirm the DEGs. Results The seminiferous tubules’ basement membrane thickens with age in healthy testes. As the period of cryptorchidism in the cryptorchid testis extended, the seminiferous tubules significantly atrophy, the number of spermatogenic cells declines, and the amount of interstitial fibrous tissue increases in comparison to normal tissues. The number of germ cells per cross-section of seminiferous tubules was significantly lower in cryptorchidism than in normal testicular tissues, according to immunofluorescence staining, but the number of Sertoli cells remained stable. RNA sequencing analysis identified 1150 differentially expressed genes (DEGs) between cryptorchidism and normal testicular tissues (fold change >2 and p<0.05), of which 61 genes were noticeably upregulated and 1089 were significantly downregulated. These genes were predominantly linked to sperm development and differentiation, and fertilization, according to GO analysis. Meiosis pathways were significantly downregulated in cryptorchidism, according to KEGG pathway analysis and GSEA (P<0.001). PPI analysis was used to identify the top seven downregulated hub genes (PLCZ1, AKAP4, IZUMO1, SPAG6, CAPZA3, and ROPN1L), which were then further verified by qPCR. Discussion By describing the histological changes and differential gene expression patterns in adult cryptorchid patients of different age groups, we discovered the progression mechanisms of undescended testes in adults with aging and identified seven significantly downregulated hub genes (PLCZ1, AKAP4, IZUMO1, SPAG6, CAPZA3, and ROPN1L) in cryptorchid testis compared to normal testicular tissues. These genes played a role in the process of spermgenesis and are directly linked to the steady decline in fertility caused by cryptorchidism. Our study provided a better understanding of the molecular mechanisms underlying the loss of spermatogenesis in adult cryptorchidism, and give support for the development of adult cryptorchidism treatments.